2004
DOI: 10.1007/s00442-004-1689-x
|View full text |Cite
|
Sign up to set email alerts
|

Dead wood biomass and turnover time, measured by radiocarbon, along a subalpine elevation gradient

Abstract: Dead wood biomass can be a substantial fraction of stored carbon in forest ecosystems, and coarse woody debris (CWD) decay rates may be sensitive to climate warming. We used an elevation gradient in Colorado Rocky Mountain subalpine forest to examine climate and species effects on dead wood biomass, and on CWD decay rate. Using a new radiocarbon approach, we determined that the turnover time of lodgepole pine CWD (340+/-130 years) was roughly half as long in a site with 2.5-3 degrees C warmer air temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 50 publications
(55 reference statements)
7
119
2
Order By: Relevance
“…However it must be noted that while the albedo radiative forcing component will occur immediately, as will a reduction in net ecosystem carbon uptake due to a stand reduction in leaf area index and associated productivity, a substantial lag will occur before killed trees fully decompose (the committed CO 2 emissions). The turnover time for lodgepole pine coarse woody debris in the Colorado Rocky Mountains can be on the order of hundreds of years, ranging from 340 ± 130 yr to 630 ± 410 yr depending on temperature Kueppers et al, 2004). This time lag between albedo and carbon radiative forcing is important to recognize.…”
Section: Discussionmentioning
confidence: 99%
“…However it must be noted that while the albedo radiative forcing component will occur immediately, as will a reduction in net ecosystem carbon uptake due to a stand reduction in leaf area index and associated productivity, a substantial lag will occur before killed trees fully decompose (the committed CO 2 emissions). The turnover time for lodgepole pine coarse woody debris in the Colorado Rocky Mountains can be on the order of hundreds of years, ranging from 340 ± 130 yr to 630 ± 410 yr depending on temperature Kueppers et al, 2004). This time lag between albedo and carbon radiative forcing is important to recognize.…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted as essential stock of biomass and carbon pool (Arthur, Fahey 1992;Bradford et al 2009;Domke et al 2011) that need to be considered in inventories and evaluated under the Framework Convention for UN climate change. Kueppers et al (2004) studied the dead wood biomass and the rate of decay in altitude gradient. According to Oswalt, Brandeis (2008), the dead wood is an important part of the total biomass and should be also considered when assessing carbon stocks.…”
Section: Introduction Uvodmentioning
confidence: 99%
“…Similarly, Lombardi et al (2013) found no relationship between the age of CWD and the chemical properties of decay classes 1-3. The main explanation for this unexpected finding is that there is probably a time lag between the death of a standing tree and its contact with the soil (Kueppers et al, 2004;Zielonka, 2006;Lombardi et al, 2013). Standing dead trees, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have used radiocarbon dating to date the last recognisable ring of deadwood. For example, Kueppers et al (2004) estimated the turnover time of lodgepole pine along a subalpine elevation gradient and Krüger et al (2014) compared tree-ring cross-dating and radiocarbon dating, demonstrating that the two techniques produce comparable results. The decay rate can be estimated by relating the time since death to the density loss or mass loss of deadwood during a given time period (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation